Globalization, Negotiation, and the Failure of Transformation in South Africa - Allen, Michael H. author. aut Link
XV, 236 p.
Keywords: The book explains the social forces, forms of consciousness and structural constraints that undermined Apartheid, preserved national unity and yet, later constrained democratic sovereignty, as the imperatives of global markets clashed with the prior aspirations of the democratic revolution.